EPCAM+CD45+ cells in ascitic fluid of patients with ovarian cancer: a relationship with tumor marker levels and tumor grade - A. V. Kozik; E. V. Kaigorodova; M. Yu. Grishchenko; S. V. Vtorushin; A. L. Chernyshova (Сибирский онкологический журнал, 2022)
Purpose of the study: to assess the relationship between atypical/hybrid forms of EpCAM+CD45+ cells in ascitic fluid of ovarian cancer patients and the levels of cancer markers, such as CA125 and HE4, and the tumor grade. Material and methods. The study included 48 patients with newly  diagnosed ovarian cancer (42 patients with stage Ic–IV ovarian cancer and 6 patients with borderline ovarian tumors (Bots). The age of the patients ranged from 36 to 76 years. the study material included ascitic fluid and blood samples. the presence of atypical/hybrid forms of EpCAM+CD45+ cells in ascitic fluid was identified by laser multicolor flow cytometry. The levels of CA125 and HE4 markers were measured by ELISA. Results. The number of EpCAM+CD45+ cells in ascitic fluid of patients with serous ovarian carcinoma was 1.02 (0.30; 2.68) cells/µl (0.55 (0.03; 4.51) cells/µl in patients with low-grade serous carcinoma (LGSC) and 1.36 (0.41; 2.68) cells/µl in patients with high-grade serous carcinoma (HGSC). The number of EpCAM+CD45+ cells in ascitic fluid of serous ovarian carcinoma was shown to have a strong  correlation with СА125 and HE4 levels in blood serum (R=0.60; р<0.01 and R=0.34; р=0.05, respectively). In the LGSC group, there was a strong direct  correlation between the number of EpCAM+CD45+ cells in ascitic fluid and the levels of CA125 and HE4 markers in blood serum (R=0.93; p<0.01 and R=0.68; p=0.03, respectively). No differences in the levels of EpCAM+CD45+ cells in ascitic fluid and CA125/ HE4 markers in blood serum between patients with HGSC and LGSC were found. the levels of atypical/hybrid forms of cells in ascitic fluid and CA125/ HE4 markers in blood serum were  significantly lower in patients with Bots than in patients with serous ovarian carcinoma (p=0.02 for EpCAM+CD45+ cells and p<0.01 for СА125/ HE4 levels). Conclusion. The relationship between the number of EpCAM+CD45+ cells in ascitic fluid and the levels of CA125 and HE4 markers in blood serum of patients with serous ovarian carcinoma was found. However, no differences in the levels of EpCAM+CD45+ cells in ascitic fluid and CA125/ HE4 markersin blood serum between patients with HGSC and LGSC were observed.